Chronic activation of FXR-induced liver growth with tissue-specific targeting Cyclin D1. Issue 15 (3rd August 2019) - Wu, Weibin; Wu, Qing; Liu, Xinmei
ABSTRACT: The nuclear receptor (FXR) plays essential roles in maintaining bile acid and lipid homeostasis by regulating diverse target genes. And its agonists were promising agents for treating various liver diseases. Nevertheless, the potential side effect of chronic FXR activation by specific agonists is not fully understood. In this study, we investigated the mechanism of FXR agonist WAY-362450 induced liver enlargement during treating liver diseases. We demonstrated that chronic ingestion of WAY-362450 induced liver hypertrophy instead of hyperplasia in mouse. Global transcriptional pattern was also examined in mouse livers after treatment with WAY-362450 by RNA-seq assay. Through GO and KEGG enrichment analyses, we demonstrated that the expression of Cyclin D1 ( Ccnd1 ) among the cell cycle-regulating genes was notably increased in WAY-362450-treated mouse liver. Activation of FXR-induced Ccnd1 expression in hepatocyte in a time-dependent manner in vivo and in vitro . Through bioinformatics analysis and ChIP assay, we identified FXR as a direct transcriptional activator of Ccnd1 through binding to a potential enhancer, which was specifically active in livers. We also found active histone acetylation was essential for Ccnd1 induction by FXR. Thus, our study indicated that activation of FXR-induced harmless liver hypertrophy with spatiotemporal modulation of Ccnd1 . With a better understanding of the mechanism of tissue-specific gene regulation by FXR, it is beneficial for development and appropriate application of its specific agonist in preventing hepatic diseases.